Potential Tools for Blended Learning in Mathematics Courses. - Chong , Chee Jiun (National Higher Education Research Institute, Universiti Sains Malaysia, 2016)

(untitled)
The development of smartphone innovations has shifted users’ dependency on bulky computers to a smaller pocket-size computing device that ease their daily tasks. In the first quarter of year 2014, Lenovo reported that the sales of their smartphones began to exceed the sales of personal computers globally (Anatol, 2014). In Malaysia, it is visible that there is a rapid shift in the manner in which things are done conventionally.